Integrate f(x): f(x) = (3x +2) / (x^2 - 5x +6)

Split into partial fractions: (3x +2) / (x2 - 5x +6) = A / (x-3) + B / (x-2) => 3x + 2 = A(x-2) + B(x-3) let x = 2: 8 = -B => B = -8 let x = 3: 11 = A => A = 11 Now we can integrate f(x) = 11 / (x-3) - 8 / (x-2): Giving: 11 ln(x-3) - 8 ln(x-2) + C

Answered by Oliver H. Maths tutor

5049 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the equation of the tangent line to the graph of y=2x^4-7x^3+x^2+3x when x=5


Simplify (3x^2-x-2)/(x^2-1)


Why is the differential of a constant zero?


What is the Product Rule?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences